Long‐term functional outcome analysis in a large cohort of patients after radical prostatectomy. Issue 7 (22nd March 2018) - Grabbert, Markus; Buchner, Alexander; Butler‐Ransohoff, Christopher; Kretschmer, Alexander; Stief, Christian G.; Bauer, Ricarda M.
Abstract : Introduction: Goal of the study was an analysis of functional outcomes after radical prostatectomy (RP) in a large cohort of patients. Methods: Functional outcomes were assessed with the ICIQ‐SF questionnaire and daily pad‐usage for the evaluation of stress urinary incontinence (SUI) as well as with the IIEF‐5 score for the evaluation of erectile dysfunction (ED). Statistical analysis included log‐rank test, Mann‐Whitney‐Test, ANOVA test and logistic regression ( P < 0.05). Results: In total 4003 patients were included in the study. Median follow‐up was 42 months (min. 2‐max. 147 mo.). Regarding ED, an IIEF‐5 score of ≥20 was reached by 39% of patients. Regarding SUI, 55% stated that they needed no pads, 21% of patients needed one pad per day. 33% of patients reported of no incontinence (0 p. in ICIQ), 26% of patients reported of a mild incontinence (1‐5 p. in ICIQ). Patientś global impression of their overall health respectively patientś subjective quality of life were assessed with the EORTC QLC‐C30 and were both high with a median of six points (on a scale of 1‐7). In multivariate analysis time since surgery could be identified as independent risk factors on QOL ( P = 0.0028), IIEF‐5 ( P = 0.0149), ICIQ ( P < 0.001), and pads per day ( P < 0.001). Conclusions: Our data show a good continence status, a clearly impaired erectile function but overall a good quality of life after surgery. In summary older patients—with an advanced tumor and adjuvant radiation therapy—were at highest risk for an impaired functional outcome.